Phantom warriors book ll - Linderer, Gary A. (Ballantine Books, 2001)
MORE GRIPPING, NO-HOLDS-BARRED LRRP ACCOUNTS FROM THE FRONT LINES During the Vietnam War, few combat operations were more dangerous than LRRP/Ranger missions. Vastly outnumbered, the patrols faced overwhelming odds as they fought to carry out their missions, from gathering intelligence, acting as hunter/killer teams, or engaging in infamous "Parakeet" flights' actions in which teams were dropped into enemy areas and expected to "develop" the situation. PHANTOM WARRIORS II presents heart-pounding, edge-of-your-seat stories from individuals and teams. These elite warriors relive sudden deadly firefights, prolonged gun battles with large enemy forces, desperate attempts to help fallen comrades, and the sheer hell of bloody, no-quarter combat. The LRRP accounts here are a testament to the courage, guts, daring, and sacrifice of the men who willingly faced death every day of their lives in Vietnam.